2010
DOI: 10.1186/1758-2652-13-s4-p45
|View full text |Cite
|
Sign up to set email alerts
|

48‐week efficacy and safety of transitioning virologically stable HIV‐1 patients from nevirapine IR 200 mg BID to nevirapine XR 400 mg QD (TRANxITION)

Abstract: 7‐11 November 2010, Tenth International Congress on Drug Therapy in HIV Infection, Glasgow, UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…At 48 weeks, virologic response was achieved in 262 of 295 patients treated with NVP-XR and 131 of 148 patients treated with NVP-IR (88.8% vs 88.5%, 0.3% difference; 95% CI: À6.1-6.7). 6 Again, NVP-XR was noninferior to NVP-IR treatment, and this outcome was further supported by consistent results from time to loss of virologic response and snapshot analyses, as defined by the US Food and Drug Administration (FDA).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…At 48 weeks, virologic response was achieved in 262 of 295 patients treated with NVP-XR and 131 of 148 patients treated with NVP-IR (88.8% vs 88.5%, 0.3% difference; 95% CI: À6.1-6.7). 6 Again, NVP-XR was noninferior to NVP-IR treatment, and this outcome was further supported by consistent results from time to loss of virologic response and snapshot analyses, as defined by the US Food and Drug Administration (FDA).…”
mentioning
confidence: 71%
“…Results from 24 weeks of follow-up have recently been published 5 and 48-week results were presented at the 10th International Congress on Drug Therapy in HIV Infection. 6…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TRANxITION trial [49], an openlabel, 2:1 randomized, parallel group study, demonstrated the non-inferiority of switching HIV-1-infected patients from NVP IR based regimen to NVP XR based regimen (Table 1).…”
Section: Patients With Viral Suppressionmentioning
confidence: 98%
“…Daher sollten Frauen mit CD4 + -Zellzahlen > 250/µl und Männer mit einer CD4 + -Zellzahl > 400/µl in der Initialtherapie kein Nevirapin erhalten [26]. Die Darreichungsform mit verzöger-ter Freisetzung erlaubt eine 1-mal tägliche Einnahme und ist seit 11/2011 in Deutschland verfügbar [2,15].…”
Section: Nevirapin (Viramune®)unclassified